Analisis Pengendalian Persediaan Bahan Baku Tebu Dalam Pembuatan Gula Pasir di Pabrik Gula Bone Arasoe - A. Reski Sanjaya. S; St Habibah St Habibah (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
This research was conducted to determine inventory control carried out by the Arasoe Sugar Factory. because of seeing the vast area of planting raw materials managed by the Arasoe sugar factory, the researchers are interested to find out about how the company manages the inventory to remain safe. we can see good control from inventory control carried out, production targets that have been scheduled every year, good inventory of raw materials, and inspection of raw materials to match the quality of production targeted each year. Then create a condition of inventory control to always be safe. Based on the narrative of several employees of the Bone Arasoe Sugar Factory, namely by estimating, the interpretation of all raw materials is ready to cut before production. Inventory control is carried out at all times by the parties responsible for their respective fields.